The Effect of 12-Week Endurance Training on Lipid Profiles and Fat Percentage of Overweight Girls - Bakhtyar Tartibian; Mehdi Kushkestani; Shiva Ebrahimpour Nosrani (Allameh Tabataba'i University Press, 2019)
Background and Purpose: Overweight and obesity in childhood are associated with the potential risk of cardiovascular disease and metabolic syndrome in adulthood. The purpose of this study was to investigate the effect of 12 weeks of moderate endurance training on lipid profile and body composition of overweight girls. Material and Method: The present study was semi-experimental with pre-test and post-test design, in which 19 overweight girls aged 8 to 12 were randomly selected. Before and after intervention, body composition of subjects was measured under fasting conditions by BODY LOGIC BODY FAT ANALYZER and biochemical indices were measured and recorded by enzyme-calorimetric method. Results: Statistical analysis showed that 12 weeks of endurance training resulted in a significant reduction in triglycerides levels (p<0.025) and body fat percentage (p<0.002), while no significant change was found in cholesterol serum levels and body mass index. Conclusions: The findings of this study suggested that moderate intensity endurance training lead to improvement of body composition and biochemical parameters related to obesity in overweight girls, which reflected the vital role of these training in preventing obesity and related cardiovascular diseases among children and adolescents.